Biofuels and synthetic fuels in the US and China: A review of Well-to-Wheel energy use and greenhouse gas emissions with the impact of land-use change - Yan, X; Inderwildi, O; King, D (2010)
Alternative transportation fuels are projected to grow substantially due to energy security concerns especially in the US and China. Moreover, some of these fuels can potentially reduce greenhouse gas (GHG) emissions from the transportation sector and hence, can help to mitigate climate change. We present a comprehensive review on Well-to-Wheel fossil fuel use and GHG emissions of biofuels and synthetic fuels in the US and China including emissions from land-use change. Our results are carefully benchmarked to the emissions caused by crude oil-derived fuels as well as synthetic fuels from fossil feedstocks in order to estimate the potential emission reduction or increase. The review strongly suggests that biofuels and synthetic fuels can contribute to GHG mitigation in the transport sector only if appropriate feedstocks are used and emissions from land-use change are minimised. © 2010 The Royal Society of Chemistry.